Impact of Inner Dopants on Structural, Optical and Mechanical Properties of Unadulterated L-Threonine Manganese Acetate - Ahamed, N.I.; Anburaj, D.B.; Nedunchezhian, G. (The Nucleus, 2022)
In this work, equal molar ratio of L-Threonine and Manganese Acetate (LTMA) and 0.2 molar of Zn2+, Cd2+ and Pb2+ doped LTMA single crystals were grown in aqueous solutions using slow evaporation technique. These crystals were subjected to various studies including single crystal X-ray diffraction, powder X-ray diffraction, FTIR, UV-vis, energy dispersive X-ray spectroscopy (EDX) and microhardness test. The cell length and interfacial angles α, β, and γ of the grown crystals were determined. EDX study confirms the placing of dopant ions Zn2+, Cd2+ and Pb2+ in the host material LTMA. FTIR analysis reported the functional group and UV-vis was carried out to study the optical behavior of the grown crystals. UV-vis studies determined the increasing energy band gap from 4.6 eV to 6.5eV and transmittance spectrum determined the lower cutoff wavelength of the grown crystals as 267 nm for the pure LTMA and ~200 nm for the doped LTMA crystals. Mechanical behavior of the crystals was studied by Vicker’s Microhardness study and their roughnesses were also reported.